Government debt in economic thought of the long 19th century - Carl-Ludwig Holtfrerich (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2013)
[Introduction] The first half of the long 19th century covers the publication of Adam Smith's 'Wealth of Nations' in 1776 through the work of subsequent representatives of classical political economy in Great Britain. The second half of that long century is marked by the contributions of German economists to public finance theory spanning the sixty years preceding the First World War. In this paper I will contrast the views of four classical British economists regarding the issue of public debt, namely those of Adam Smith, David Ricardo, Thomas Robert Malthus and John Stuart Mill, with those of three German economists, Carl Dietzel, Lorenz von Stein, and, with the internationally prominent (at least up to the First World War), Adolph Wagner. The position of British economists of the classical school that government debt was an impediment to economic progress is relatively familiar. Maybe due to their harsh judgment they treated the issue only in passing. In contrast, considerably less well-known today are the contributions of these three German economists who published entire books devoted to the issue of public debt with a subtly differentiated analysis and who were led to significantly more favorable assessments of the use of debt finance by governments. Before outlining the views of the classical economists in Great Britain, I begin with a brief discussion of the origins and magnitude of the British debt problem, the times when the main representatives of the British classical school shaped their views. Having the times and doctrines of English political economy before us, we move to consider each of the three German economists to see what led them to discover a more positive role for the use of debt in a system of public finance. The paper concludes by highlighting the main differences between the two traditions.
Keywords: 330